Perceived Choices of Graduation among Master Students: Expectancy-Task Value Theoretical Perspective - Fidelis Chosa Kastuhandani; Ke Sambo; Harth Bunhe (International Journal of Educational Review, 2022)
This study investigated whether motivational beliefs (expectancy of success and value in research and practice related tasks) among master students predict the achievement related choices for graduation (thesis or non-thesis) and examined the likelihood of those motivational beliefs in thesis and non-thesis preferring group. Participants studied in various master programs of two universities in Cambodia completed the questionnaires about their expectancy of success and values toward research and practice related tasks and preferences of graduation. Results of logistic regression analysis revealed that, among the motivational beliefs, only cost in research indicated a significant predictor of graduation preferences (p = .003). Furthermore, the associated likelihood of thesis preferring group was anchored at students who have higher positive beliefs on cost in research (ß = 2.386, p = .003, Exp (ß) = 10.867, Odd = 986.9), interest in research (ß = .933, p = .431, Exp (ß) = 2.542, Odd = 154.2), utility in practice (ß = .835, p = .226, Exp (ß) = 2.306, Odd = 130.6), and attainment in research (ß = .218, p = .699, Exp (ß) = 1.243, Odd = 24.3) although the rest of expectancy-values components was not completely discriminated in its membership model. Implications of the findings to graduate programs and future direction are discussed.